Roh Kudus dan ketekunan belajar: Eksplorasi spiritualitas pembelajar melalui permodelan komunitas gereja perdana dalam narasi Kisah Para Rasul 2:42 - Sitompul, Baginda (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
This article examines the relationship between the work of the Holy Spirit and the development of spiritual learning within contemporary Christian education contexts. Drawing upon the model of the early church community depicted in Acts 2:42, this research investigates how perseverance in the apostles' teaching can be constructed as a Christian educational paradigm that stimulates students to develop learning perseverance. Through exegetical analysis of the Acts 2:42 text, a literature review on the Holy Spirit's role in learning, and a synthesis of Christian educational theology, this study proposes a pneumatological framework for understanding learning perseverance as a spiritual practice empowered by the Holy Spirit. The study argues that authentic learning experiences within Christian communities are not merely cognitive activities but transformative spiritual experiences that occur through the dynamic interaction between the Holy Spirit, the Word, and the learning community. Implications for contemporary Christian educational practice are also discussed, highlighting the importance of creating Spirit-centered learning environments where learning perseverance is understood and experienced as a response to the work of the Holy Spirit. Abstrak Artikel ini mengeksplorasi hubungan antara karya Roh Kudus dan pengembangan spiritualitas pembelajaran dalam konteks pendidikan Kristiani kontemporer. Dengan mengambil model komunitas gereja perdana yang digambarkan dalam Kisah Para Rasul 2:42, penelitian ini menyelidiki bagaimana ketekunan dalam pengajaran para rasul dapat dikonstruksikan sebagai sebuah paradigma pendidikan Kristiani yang menstimulasi murid untuk mengembangkan ketekunan belajar. Melalui analisis eksegesis teks Kisah Para Rasul 2:42, tinjauan literatur tentang peran Roh Kudus dalam pembelajaran, dan sintesis teologi pendidikan Kristiani, penelitian ini mengusulkan kerangka kerja pneumatologis untuk memahami ketekunan belajar sebagai praktik spiritual yang diberdayakan oleh Roh Kudus. Studi ini berargumen bahwa pengalaman pembelajaran autentik dalam komunitas Kristiani tidak hanya merupakan aktivitas kognitif tetapi juga pengalaman spiritual transformatif yang terjadi melalui interaksi dinamis antara Roh Kudus, Firman, dan komunitas pembelajar. Implikasi bagi praktik pendidikan Kristiani kontemporer juga dibahas, menyoroti pentingnya menciptakan lingkungan pembelajaran yang berpusat pada Roh Kudus di mana ketekunan belajar dipahami dan dialami sebagai respons terhadap karya Roh Kudus.